INTEGRITY AND PERFORMANCE OF MOSQUE ADMINISTRATOR IN MALAYSIA - Marziana Madah Marzuki; Mohd Hisham Mahamud; Rosliza Bahari; Suzana San; Othman Zailani Hassan; Wan Zurina Nik Abdul Majid (Journal of Islamic, Social, Economics and Development, 2024)
The mosque is very significant in shaping and developing the success of ummah. Generally, the issue of integrity is said to be directly linked with performance. This study aims to examine the relationship between integrity and performance of mosque administrator in Kelantan. This research was conducted using quantitative method using the questionnaire. The data collected then be analysed using SPSS. Results show that integrity has a direct effect on the performance of the mosque administrator where it shapes on how the mosque is being governed. This study provides implications to the Kelantan State especially to Majlis Agama dan Istiadat Melayu Kelantan (MAIK) to cater the issue of integrity and link with the mosque administrator’s performance. The novelty of the research and the original study on integrity in mosque administration contributes the originality of this work.